Pengaruh Perubahan Luas Tutupan Lahan Hutan Terhadap Karakteristik Hidrologi DAS Citarum Hulu - Andi Gustiani Salim; I Wayan S Dharmawan; Budi Hadi Narendra (School of Postgraduate Studies, Diponegoro Univer, 2019)
The decline in water resources and the occurrence of various hydrological disasters in the Citarum watershed indicate the need to restructure the components inside the watershed, especially land cover in the upper watershed area. This study aims to determine the effect of forest land cover on the hydrological parameters of the upstream Citarum watershed through simulations of the SWAT (Soil and Water Assessment Tool) model. The results showed that the forest cover in the Citarum watershed was only 15.96% of the watershed area and only 4.94% was located in the Upper area. The Flow Rate Coefficient of the upstream Citarum watershed is 31.4, the annual average surface flow and annual erosion are 933.03 mm and 517.9 tons/ha respectively. The simulation from several scenarios shows that a decreasing in forest area can increase discharge and surface runoff, whereas an increase in forest area will increase soil infiltration and evapotranspiration. Decreasing forest area by 10% from existing conditions caused 58% of rainwater to become surface runoff. The large number of discrepancies between the existing conditions and the directions in the RTRWP will require a long time and large costs to adjust so that the short-term alternative that can be done is to convert dryland agricultural cover to the forest to reach forest cover of at least 45% of the land area in the upstream area and can optimize the hydrological function of the watershed.